Analisis Pengaruh Literasi Keuangan Dan Inklusi Keuangan Terhadap Keputusan Investasi UMKM Di Pedesaaan Madura - Rifaldi, Moh; Kurniawan, Moh Zaki (JURNAL ADMINISTRASI KANTOR; Vol 12 No 1 (2024): Jurnal Administrasi Kantor (Juni 2024)DO - 10.51211/jak.v12i1.2699, 2024)
The research was conducted to find out how to, analyze the influence of financiall literacy and financial, inclusion on MSME investment decisions in rural Madura. The population in the study were people in Madura, especially Bangkalan and Sampang Regencies. The sampling technique used a purposive sampling method, with a sample of 70 respondents in the study. The research results show that financial literacy has no effect on MSME investment decisions in rural Madura, while financial inclusion has a positive and significant effecty on MSME investmentt decisions in rural Madura.   Keywords : Financial Literacy, Financial Inclusion, Investment Decision, MSME.